Identification of QTLs and a candidate gene affecting rice grain volume via high-density genetic mapping - Sun, Zhiguang; An, Hongzhou; Qiu, Zeyu; Li, Jingfang; Li, Jian; Yang, Bo; Liu, Jinbo; Chen, Tingmu; Zhang, Yuqin; Lu, Baiguan; Liu, Yan; Wang, Baoxiang; et al. (Frontiers in Plant Science, 2025)
IntroductionGrain volume is a key agronomic trait of rice. It is coordinately determined by grain length, width, thickness, and roundness, which influences the rice yield and quality, yet the molecular mechanism is still not fully understood.MethodsIn this study, a mapping population of Ludao (weedy rice) and Guangbaixiangzhan (GBXZ) was developed in Lianyungang, Jiangsu province, China, and was employed to construct a high-density genetic map by use of the RICE 1 K mGPS chip in 2021. The mapping of QTLs was carried out with IciMapping software using the inclusive composite interval mapping (ICIM) method.Results and discussionA total of eight QTLs for grain volume, explained 4.22–19.75% of the total phenotypic variation, were detected with LOD scores ranging from 3.33 to 13.25. Among these loci, five are known genes or loci related to grain size, and three loci, qGV4-2, qGV7-1, and qGV7-2, were newly identified. The major QTL, qGV7-2, explained the highest phenotypic variation, was validated using NIL pairs. By combining gene functional annotation, gene expression analysis and sequence comparison within the mapping interval of qGV7-2, a candidate gene (LOC_Os07g15540), encoding an ethylene receptor, OsETR4, was identified. Further haplotype–phenotype analysis revealed this gene to be significantly associated with grain length, width, and thousand-grain weight. Thus we identified LOC_Os07g15540 as the most likely candidate gene. Taken together, our findings provide a basis for functional research on qGV7-2, and broaden our understanding of role of genetic factors in regulating grain volume, thus providing an important resource for yield improvement in rice.